High salivary testosterone‐to‐androstenedione ratio and adverse metabolic phenotypes in women with polycystic ovary syndrome. (23rd January 2017) - Münzker, J.; Lindheim, L.; Adaway, J.; Trummer, C.; Lerchbaum, E.; Pieber, T.R.; Keevil, B.; Obermayer‐Pietsch, B.
Summary: Background: Polycystic ovary syndrome (PCOS) is characterized by a combination of hormonal and metabolic disturbances, such as insulin resistance, glucose intolerance, anovulation and hyperandrogenism. Clinical phenotypes of PCOS show different patterns of steroid hormones that have been investigated to some extent. This study aimed to establish a liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for the quantification of salivary testosterone and androstenedione and to describe the salivary testosterone‐to‐androstenedione (T/A4) ratio as a new tool for the assessment of hyperandrogenism and metabolic health. Material and methods: Saliva and serum samples of 274 patients with PCOS and 51 healthy women were used for the quantification of steroid hormones. A comprehensive clinical and metabolic assessment was performed. Salivary testosterone and androstenedione were measured via LC‐MS/MS. The salivary T/A4 ratio was calculated and correlated with hormones and metabolic parameters. Results: Salivary testosterone ( P < 0·001), androstenedione ( P < 0·001) and the salivary T/A4 ratio ( P < 0·001) were significantly higher in patients with patients compared to healthy women. In patients with PCOS, a high salivary T/A4 ratio was associated with an adverse metabolic phenotype, that is glucose intolerance ( P = 0·019), insulin resistance ( P < 0·001), metabolic syndrome ( P < 0·001), obesity ( P < 0·001) and oligo‐/anovulation ( P = 0·001). Significant correlations of the salivary T/A4 ratio with adverse metabolic parameters were found. Conclusion: Quantification of salivary androgens provides an attractive alternative to serum analysis and helps in characterizing metabolic health in women with PCOS. Our data show a strong link between a high salivary T/A4 ratio and an adverse metabolic phenotype in patients with PCOS.